Electrochemical Conversion of CO2 to Syngas with Controllable CO/H2 Ratios over Co and Ni Single‐Atom Catalysts. (9th January 2020) - He, Qun; Liu, Daobin; Lee, Ji Hoon; Liu, Yumeng; Xie, Zhenhua; Hwang, Sooyeon; Kattel, Shyam; Song, Li; Chen, Jingguang G.
Abstract: The electrochemical CO2 reduction reaction (CO2 RR) to yield synthesis gas (syngas, CO and H2 ) has been considered as a promising method to realize the net reduction in CO2 emission. However, it is challenging to balance the CO2 RR activity and the CO/H2 ratio. To address this issue, nitrogen‐doped carbon supported single‐atom catalysts are designed as electrocatalysts to produce syngas from CO2 RR. While Co and Ni single‐atom catalysts are selective in producing H2 and CO, respectively, electrocatalysts containing both Co and Ni show a high syngas evolution (total current >74 mA cm −2 ) with CO/H2 ratios (0.23–2.26) that are suitable for typical downstream thermochemical reactions. Density functional theory calculations provide insights into the key intermediates on Co and Ni single‐atom configurations for the H2 and CO evolution. The results present a useful case on how non‐precious transition metal species can maintain high CO2 RR activity with tunable CO/H2 ratios. Abstract : Die Produktion von Synthesegas mit hoher Ausbeute und einem für bestehende thermochemische Synthesen geeigneten CO/H2 ‐Verhältnis gelingt durch die gezielte Abstimmung einzelner Atome, die in N‐dotierte Kohlenstoffe eingebettet sind.